European Union and Romanian Tourism – ß and s Convergence in the Economic Development Regions of Romania - Gina Ionela Butnaru; Valentin Niță (Amfiteatru Economic Journal, 2016)
At present, both in Romania and in Europe, tourism tends to become one of the biggest industries, with great development possibilities in the future. The economic development of Romania including tourism benefits from the support of the European Union, and has the purpose to reduce the gaps in this concern, compared to both the European Union average and more developed countries. The purpose of this paper is to analyse ß and s convergence in the 8 Economic Development Regions of Romania by a tourism approach. The concept of ß-convergence represents the process of quicker development of poor regions than the rich ones, and s-convergence is evaluating the process of decrease of regional economic disparities in time. The analysis based on ß-convergence was performed using econometric modelling techniques of linear correlation. For s-convergence, we measured the dispersion of real GDPT per in habitant by the use of the variation coefficient t - . The purpose is to check the hypothesis according to which the ß-convergence approach and the s- convergence concept can lead to different results for the Economic Development Regions of Romania. The period analysed is between 2007 and 2013.
Keywords: D00; N90; R19; R39; 330; ß-convergence; s-convergence; Romanian tourism; Economic Development Regions of Romania